Morphological Evaluation and Selection of Gladiolus (Gladiolus×Hybridus L.) Hybrids for Commercial Traits - Swaroop, Kishan; Singh, K. P.; Kumar, Arun; Misra, R. L. (International Journal of Economic Plants, 2022)
This experiment was conducted with twenty-five gladiolus hybrids along with a check at the research farm of the Division of Floriculture & Landscaping, ICAR, Indian Agricultural Research Institute, New Delhi to study the performance and suitability of hybrids for different traits. The mean performance of gladiolus hybrid data was highly significant for all the characters studied; however, the results indicated that early flowering was seen in six hybrids such as Smokey Lady×Heady Wine Open seedling, The Berton Open seedling, Green Willow× Oscar, Shweta×Regency, Canada×Green Finch and Howard×Rose Time Steamboat and ranging from 82.33 to 86.00 days after planting. The maximum plant height 127.66 cm, spike length 116.00 cm and rachis length 63.33 cm were observed in Rose Time Steamboat hybrid, but number of florets per plant 19.33 was recorded in Canada×Green Finch hybrid. The number of corms i.e., three or more than three were recorded in seven hybrids namely; Oscar×Green Willow, (Snow Princess×Ratna)×Urmil, Smokey Lady×Mayur, Snow Princess.×Howard, Berlew Open seedling (Dark orange), Rose Time Steamboat Open seedling and Pink Parassol Open seedling respectively; whereas number of cormels in the range of 50.00 – 64.00 were recorded in five hybrids including check variety.